Variations microclimatiques et effet de la végétation dans la ville aride de Ghardaïa, Algérie - Rachid Amieur; Djamila Rouag Saffidine; Christiane Weber (VertigO)
Characterizing urban climate in hot arid cities is a key step to understand the interactions of climatic variables with the built-up and the vegetation. Extreme heat waves in summer are a strong stress especially for heat-vulnerable populations such as young children, the elderly and the sick. Urban Heat Island (UHI) in hot arid regions shows some specific features compared to other regions. Vegetation is known to play a role in alleviating urban heat island especially in hot arid climates. This study aims to analyse intra-urban microclimatic variations and the impact of vegetation in the arid city of Ghardaïa via in-situ measurements. The thermal behavior of measurement sites varies between urban heat island and cool island. It was detected an "archipelago" of heat throughout the city. The maximum intensity of UHI is 2.98 ° C. As for the intra-urban differences, the vegetation produces a maximum PCI of 5.61 ° C. The minimum night-time temperature is above 30 ° C, well above the thermal comfort limit. The moderating effect of vegetation is mainly due to the shade provided by tree canopy. Vegetated sites do not show a significant difference in humidity compared to other built-up sites. It seems that a denser urban vegetation cover would further improve comfort conditions in the city.